Impact of confirmatory test results on subtype classification and biochemical outcome following unilateral adrenalectomy in patients with primary aldosteronism - Daneshpour, Hediyeh; Brüdgam, Denise; Stüfchen, Isabel; Heinrich, Daniel Alexander; Bidlingmaier, Martin; Beuschlein, Felix; Kürzinger, Lydia; Williams, Tracy Ann; Reincke, Martin; Schneider, Holger; Adolf, Christian (Frontiers in Endocrinology, 2024)
Primary aldosteronism (PA) is the most common form of endocrine hypertension. According to the Endocrine Society Practice Guidelines, the diagnosis of PA requires a pathological screening test result and non-suppressible aldosterone levels during confirmatory testing. Sequential testing with more than one confirmatory test may result in discordant test results.We investigated the association of discordant results of captopril challenge test (CCT) and saline infusion test (SIT) on patient subtype classification by adrenal vein sampling (AVS) and outcome in 111 consecutive patients from the German Conn's Registry. Concordance was defined as non-suppressible aldosterone levels upon both tests, while discordance was defined as conflicting test results. Patients with unilateral disease were offered adrenalectomy (ADX).Biochemical and clinical outcomes were assessed using the PASO criteria.85 of 111 (77%) patients had concordant results of CCT and SIT. Although baseline characteristics were comparable between patients with concordant and discordant tests, the latter had significantly lower aldosterone levels after testing (CCT: 170 vs. 114pg/ml; SIT: 139 vs. 101pg/ml; p=0.004).In 35% of patients with discordant (n=9) and 46% of concordant test results (n=39), AVS suggested lateralized PA. In 36 of 48 cases ADX was performed. 86% of patients with discordant and 72% with concordant results had complete biochemical success.The use of two confirmatory tests in patients with PA results in discordant results in approximately 23 % of cases. Patients having discordant confirmatory test results had a comparable rate of lateralized PA and underwent adrenalectomy with similar long-term outcome.